Ruptura amorosa y la depresión en un hombre de 24 años del Recinto Guayacanes - Ulloa Armijos, Julio Josel (2023)
Breakups are a very common event or situation in human development. What makes it interesting to investigate is the relationship or course that can lead to the breakup being an etiological factor to cause depression in a young adult, I feel. is capable of suffering symptoms such as sadness, anhedonia, apathy and even thoughts about death. This case study meets the objective of determining the relationship between a love breakup and the manifestation of symptoms of depression in a 24-year-old man from the Guayacanes area. In order to carry out this task, it was necessary to set the following specific objectives: analyze the emotional impact of a love breakup, measure the prevalence and severity of psychopathological symptoms and establish a treatment plan to improve mental health. This could be achieved due to the methodological application of a qualitative approach and carrying out a type of descriptive research. Based on this, the discussion and conclusions of the results were established.